Screening of transcription factors involved in fetal hemoglobin regulation using phylogenetic footprinting - Carrocini, Gisele Cristine de Souza [UNESP]; Venancio, Larissa Paola Rodrigues [UNESP]; Bonini-Domingos, Claudia Regina [UNESP] (SAGE Publications, 2015)
Fetal hemoglobin (Hb F) is an important genetic modulator of the beta-hemoglobinopathies. The regulation of Hb F levels is influenced by transcription factors. We used phylogenetic footprinting to screen transcription factors that have binding sites in HBG1 and HBG2 genes’ noncoding regions in order to know the genetic determinants of the Hb F expression. Our analysis showed 354 conserved motifs in the noncoding regions of HBG1 gene and 231 motifs in the HBG2 gene between the analyzed species. Of these motifs, 13 showed relation to Hb F regulation: cell division cycle-5 (CDC5), myelo-blastosis viral oncogene homolog (c-MYB), transcription factor CP2 (TFCP2), GATA binding protein 1 (GATA-1), GATA binding protein 2 (GATA-2), nuclear factor erythroid 2 (NF-E2), nuclear transcription factor Y (NF-Y), runt-related transcription factor 1 (RUNX-1), T-cell acute lymphocytic leukemia 1 (TAL-1), YY1 transcription factor (YY1), beta protein 1 (BP1), chicken ovalbumin upstream promoter-transcription factor II (COUP-TFII), and paired box 1 (PAX-1). The last three motifs were conserved only in the noncoding regions of the HBG1 gene. The understanding of genetic elements involved in the maintenance of high Hb F levels may provide new efficient therapeutic strategies in the beta-hemoglobinopathies treatment, promoting reduction in clinical complications of these genetic disorders.
Keywords: Beta-hemoglobinopathies; Hb F; Phylogenetic footprinting; Transcription factors